Development and Alpha Testing of QuitIT: An Interactive Video Game to Enhance Skills for Coping With Smoking Urges - Krebs, Paul (JMIR Publications Inc., 2013)
BACKGROUND: Despite many efforts at developing relapse prevention interventions, most smokers relapse to tobacco use within a few months after quitting. Interactive games offer a novel strategy for helping people develop the skills required for successful tobacco cessation. OBJECTIVE: The objective of our study was to develop a video game that enables smokers to practice strategies for coping with smoking urges and maintaining smoking abstinence. Our team of game designers and clinical psychologists are creating a video game that integrates the principles of smoking behavior change and relapse prevention. We have reported the results of expert and end-user feedback on an alpha version of the game. METHODS: The alpha version of the game consisted of a smoking cue scenario often encountered by smokers. We recruited 5 experts in tobacco cessation research and 20 current and former smokers, who each played through the scenario. Mixed methods were used to gather feedback on the relevance of cessation content and usability of the game modality. RESULTS: End-users rated the interface from 3.0 to 4.6/5 in terms of ease of use and from 2.9 to 4.1/5 in terms of helpfulness of cessation content. Qualitative themes showed several user suggestions for improving the user interface, pacing, and diversity of the game characters. In addition, the users confirmed a high degree of game immersion, identification with the characters and situations, and appreciation for the multiple opportunities to practice coping strategies. CONCLUSIONS: This study highlights the procedures for translating behavioral principles into a game dynamic and shows that our prototype has a strong potential for engaging smokers. A video game modality exemplifies problem-based learning strategies for tobacco cessation and is an innovative step in behavioral management of tobacco use.